Effect Of Financing In Sharia Business Units On Profitability And Financing Risk Management - Sofyan Halim (Journal of Islamic Economics and Social Science (JIESS), 2020)
Financing is one of the main functions of the operations of sharia banks, including those carried out by the Syari'ah Business Unit. Funds disbursed to the Syari'ah Business Unit are carried out by means of buying and selling, namely Murabaha contracts, greetings, and istisna agreements, then by investing in mudharabah contracts and musyarakah contracts and performing rental services with ijarah contracts. Syarai'ah Banking by carrying out the financing benefits from buying and selling, obtaining profit sharing from investing and obtaining rental opinions from the ijarah contract. Thus, the three types of income will produce and affect the level of profitability depending on the financial services carried out by PerbangkanSyari'ah, including those carried out by the Syari'ah Business Unit. In carrying out the financing there is an element of risk that needs to be managed properly and professionally, so that the risk can be minimized in the sense that the amount of financing that is categorized as non-current does not negatively affect profitability, as well as risk management such as non-perfomed financing with various contracts, can be minimized along with the level of collectibility for the financing that has been channeled. The researcher will also carry out various statistical tests in this study so that in this study the results of the conclusions are positive and can be useful for anyone who has an interest in this research. The study was conducted with a quantitative method, with the conclusion that there was a positive relationship between financing with murabaha, mudharabah, musyarakah and ijarah contracts towards profitability and in general also negatively affected the NPF with the understanding that even though there was an increase in financing distribution with contracts, however, risk control over the possibility of NPF occurring can be overcome except for financing with Murabaha contracts.This research is expected to be useful for stakeholders related to this research and for future researchers to be able to improve further research.